2006
DOI: 10.1080/00480169.2006.36620
|View full text |Cite
|
Sign up to set email alerts
|

The isoflavone content of commercially-available feline diets in New Zealand

Abstract: Isoflavones are present in commercially-prepared feline diets sold in New Zealand at concentrations that have elicited physiological responses in the reproductive, endocrine, and immune systems of other mammalian species. Since isoflavones appear to be a common constituent of feline diets, further investigation of the biological activities of these dietary compounds in cats is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 20 publications
1
40
1
Order By: Relevance
“…Other dietary factors that have been implicated in the pathogenesis of the feline toxic nodular goiter include dietary flavonoids, which are found in high concentrations in many cat foods (Court & Freeman 2002, Bell et al 2006. Flavonoids can act to inhibit thyroid peroxidase and have known goitrogenic properties (Divi & Doerge 1996, Köhrle 2000, Doerge & Sheehan 2002.…”
Section: Why Has Feline Nodular Goiter Reached Such Epidemic Proportimentioning
confidence: 99%
“…Other dietary factors that have been implicated in the pathogenesis of the feline toxic nodular goiter include dietary flavonoids, which are found in high concentrations in many cat foods (Court & Freeman 2002, Bell et al 2006. Flavonoids can act to inhibit thyroid peroxidase and have known goitrogenic properties (Divi & Doerge 1996, Köhrle 2000, Doerge & Sheehan 2002.…”
Section: Why Has Feline Nodular Goiter Reached Such Epidemic Proportimentioning
confidence: 99%
“…Food was withheld 18 h before oral administration of 1 soy extract tablet (approximately 0.218 g, Phytolife1 One a Day; Healthy Living, Palmerston North, New Zealand). Analysis by HPLC (Bell et al, 2006b) showed that on average, 1 tablet contained 10.17 mg genistein and 13.12 mg daidzein (as-fed) as aglycone equivalents. One-half of the daily allowance (293 kJ·kg BW -1 ·d -1 ; NRC 1986) of an isofl avone-free diet (Table 1) of each cat was offered 5 min before administering the tablet.…”
Section: Methodsmentioning
confidence: 99%
“…The diet was a nutritionally complete and balanced, moist commercial diet, which met the maintenance nutrient requirements of adult cats (AAFCO, 2009) and contained the following ingredients: selected meat byproducts and meat derived from beef, lamb, and chicken; fi sh byproduct; vegetable protein; gelling agents; calcium; coloring; and necessary vitamins. This diet was previously analyzed (Bell et al, 2006b), and no detectable isofl avones (genistein, daidzein, formononetin, and biochanin A) were found.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations